2022
DOI: 10.1021/acs.inorgchem.2c00743
|View full text |Cite
|
Sign up to set email alerts
|

Smart Multifunctional UiO-66 Metal–Organic Framework Nanoparticles with Outstanding Drug-Loading/Release Potential for the Targeted Delivery of Quercetin

Abstract: Herein, UiO-66 and its two functional analogs (with −NO 2 and −NH 2 functional groups) were synthesized, and their potential ability as pH stimulus nanocarriers of quercetin (QU), an anticancer agent, was studied. UiO-66 is a low-toxicity, biocompatible metal−organic framework with a large surface area and good stability, which can be prepared through a facile and inexpensive method. Before and after drug loading, various analyses were conducted to characterize the synthesized nanocarriers. Moreover, Monte Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 112 publications
0
25
0
Order By: Relevance
“…Hence fluctuation of Qu in plasma levels remains a major drawback for high therapeutic efficacy. 14 However, if Qu could be delivered directly to the disease sites without premature leakage into the bloodstream, then the therapeutic efficacy would be improved significantly. To attain this, there is an urgent need for a nanotechnology-based drug delivery system which can lead to sustained release, while modern drug delivery systems are designed in such a way that they facilitate multiple therapeutic modalities like photothermal therapy (PTT) and photodynamic therapy (PDT).…”
Section: Introductionmentioning
confidence: 99%
“…Hence fluctuation of Qu in plasma levels remains a major drawback for high therapeutic efficacy. 14 However, if Qu could be delivered directly to the disease sites without premature leakage into the bloodstream, then the therapeutic efficacy would be improved significantly. To attain this, there is an urgent need for a nanotechnology-based drug delivery system which can lead to sustained release, while modern drug delivery systems are designed in such a way that they facilitate multiple therapeutic modalities like photothermal therapy (PTT) and photodynamic therapy (PDT).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the development of materials with optimal CO 2 binding energies and high selectivity is a complex issue with considerable practical implications. MOFs are porous inorganic materials that have received much attention recently owing to their outstanding characteristics, such as significant surface area and porosity, thermal/chemical stability, and tunability. MOFs are considered promising materials for a variety of potential applications across various fields, including gas storage and separation, chemical sensing, biomedical applications, adsorption, and heterogeneous catalysis. They are considered as one of the most promising physical adsorbent materials in the process of separating CO 2 /CH 4 . The engineering design of MOFs for gas separation applications is currently a rapidly growing area of research. Numerous experimental and simulation-based studies have been documented involving the separation of CO 2 from CH 4 through the use of MOFs. Considering the quadrupole moment and polarizability of CO 2 , current research efforts to enhance CO 2 uptake and selectivity primarily involves strategies aimed at improving the interaction between CO 2 and the frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…85−91 Recently, a study showed that UiO-66 and its analogues with −NO 2 and −NH 2 functional groups were capable of the effective targeted delivery of QU. 92 A Zrbased MOF ([Zr 6 O 4 (OH) 4 (BTC) 2 (HCOO) 6 ]), namely, MOF-808, is a cubic framework constituted of Zr 6 (μ 3 -O) 4 (μ 3 -OH) 4 nodes connected by benzene-1,3,5-tricarboxylate (trimesic acid, BTC) ligands to form an adamantane-shaped cage with a diameter of 18 Å and a tetrahedral cage with a diameter of 4.8 Å. 93,94 All of these features make MOF-808 an excellent candidate for the incorporation of QU with a suitable molecular size (4.24 × 7.11 Å).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MOFs have been receiving increasing attention for their potential applications in gas adsorption, antibacterial activity, biocatalysis, , bioimaging , and biosensing. , MOFs are very valuable and practical porous nanostructures in drug-delivery systems because of their specific properties such as large surface areas, high pore volumes, and adjustable pore sizes. Recently, diverse MOFs such as MIL-100 (Fe), CD-MOF-1, , and UiO-66 (Zr) have been used for the delivery of antibiotics and antiinflammatory drugs . Zeolitic imidazole framework-8 (ZIF-8) and ZJU-802 were applied as carriers of doxorubicin and ibuprofen, respectively. , Among the numerous MOFs, Zr-based MOFs have been widely used as drug-delivery systems because of their high chemical stability (especially water stability), high level of biocompatibility, and high drug-loading capacity. Recently, a study showed that UiO-66 and its analogues with −NO 2 and −NH 2 functional groups were capable of the effective targeted delivery of QU . A Zr-based MOF ([Zr 6 O 4 (OH) 4 (BTC) 2 (HCOO) 6 ]), namely, MOF-808, is a cubic framework constituted of Zr 6 (μ 3 -O) 4 (μ 3 -OH) 4 nodes connected by benzene-1,3,5-tricarboxylate (trimesic acid, BTC) ligands to form an adamantane-shaped cage with a diameter of 18 Å and a tetrahedral cage with a diameter of 4.8 Å. , All of these features make MOF-808 an excellent candidate for the incorporation of QU with a suitable molecular size (4.24 × 7.11 Å).…”
Section: Introductionmentioning
confidence: 99%